Notes on Sontag - Lopate, Phillip, 1943- (Book collections on Project MUSE., 2009)
Notes on Sontag is a frank, witty, and entertaining reflection on the work, influence, and personality of one of the "foremost interpreters of ... our recent contemporary moment." Adopting Sontag's favorite form, a set of brief essays or notes that circle around a topic from different perspectives, renowned essayist Phillip Lopate considers the achievements and limitations of his tantalizing, daunting subject through what is fundamentally a conversation between two writers. Reactions to Sontag tend to be polarized, but Lopate's account of Sontag's significance to him and to the culture over.